Development of a highly sensitive method to detect translational infidelity - Hartmann, Max; Neher, Lisa; Grupp, Benjamin; Cao, Zhouli; Chiew, Chloe; Iben, Sebastian (Biology methods and protocols, 2025)
Protein homeostasis (proteostasis) is the balance of protein synthesis, protein maintenance, and degradation. Loss of proteostasis contributes to the aging process and characterizes neurodegenerative diseases. It is well established that the processes of protein maintenance and degradation are declining with aging; however, the contribution of a declining quality of protein synthesis to the loss of proteostasis is less well understood. In fact, protein synthesis at the ribosome is an error-prone process and challenges the cell with misfolded proteins. Here, we present the development of a highly sensitive and reproducible reporter assay for the detection of translational errors and the measurement of translational fidelity. Using Nano-luciferase, an enzyme 3 times smaller and 50 times more sensitive than the hitherto used Firefly-luciferase, we introduced stop-codon and amino-acid exchanges that inactivate the enzyme. Erroneous re-activation of luciferase activity indicates ribosomal inaccuracy and translational infidelity. This highly sensitive and reproducible method has broad applications for studying the molecular mechanisms underlying diseases associated with defective protein synthesis and can be used for drug screening to modulate translational fidelity.